Question
upstudy study bank question image url

Question \#3: \( \left\{\begin{array}{l}x-2 y+3 z=-25 \\ x-2 y-3 z=5 \\ 5 x+2 y-3 z=17\end{array} \quad\right. \) Use cramers rule to

Ask by Curry Valdez. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solution is \( x = -\frac{4}{3} \), \( y = \frac{13}{3} \), and \( z = -5 \).

Solution

Solve the system of equations \( x-2y+3z=-25;x-2y-3z=5;5x+2y-3z=17 \). Solve the system of equations by following steps: - step0: Solve using the substitution method: \(\left\{ \begin{array}{l}x-2y+3z=-25\\x-2y-3z=5\\5x+2y-3z=17\end{array}\right.\) - step1: Solve the equation: \(\left\{ \begin{array}{l}x=-25+2y-3z\\x-2y-3z=5\\5x+2y-3z=17\end{array}\right.\) - step2: Substitute the value of \(x:\) \(\left\{ \begin{array}{l}-25+2y-3z-2y-3z=5\\5\left(-25+2y-3z\right)+2y-3z=17\end{array}\right.\) - step3: Simplify: \(\left\{ \begin{array}{l}-25-6z=5\\-125+12y-18z=17\end{array}\right.\) - step4: Solve the equation: \(\left\{ \begin{array}{l}z=-5\\-125+12y-18z=17\end{array}\right.\) - step5: Substitute the value of \(z:\) \(-125+12y-18\left(-5\right)=17\) - step6: Simplify: \(-35+12y=17\) - step7: Move the constant to the right side: \(12y=17+35\) - step8: Add the numbers: \(12y=52\) - step9: Divide both sides: \(\frac{12y}{12}=\frac{52}{12}\) - step10: Divide the numbers: \(y=\frac{13}{3}\) - step11: Substitute the values of \(y,z:\) \(x=-25+2\times \frac{13}{3}-3\left(-5\right)\) - step12: Simplify: \(x=-\frac{4}{3}\) - step13: Calculate: \(\left\{ \begin{array}{l}x=-\frac{4}{3}\\y=\frac{13}{3}\\z=-5\end{array}\right.\) - step14: Check the solution: \(\left\{ \begin{array}{l}x=-\frac{4}{3}\\y=\frac{13}{3}\\z=-5\end{array}\right.\) - step15: Rewrite: \(\left(x,y,z\right) = \left(-\frac{4}{3},\frac{13}{3},-5\right)\) The solution to the system of equations using Cramer's rule is: \[ (x,y,z) = \left(-\frac{4}{3},\frac{13}{3},-5\right) \] or \[ (x,y,z) = (-1.3,4.3,-5) \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

Cramer's Rule is a powerful method for solving systems of linear equations using determinants. To apply it, you'll need to calculate the determinant of the coefficient matrix and the determinants of matrices formed by replacing columns with the constants on the right-hand side. In this case, you would form a \(3 \times 3\) matrix from the coefficients of \(x\), \(y\), and \(z\), and then compute the necessary determinants to find values for \(x\), \(y\), and \(z\). A common mistake when using Cramer's Rule is forgetting to correctly substitute the right column in your determinant calculation. Make sure you double-check your matrices before calculating the determinants! Additionally, ensure that the original coefficient matrix is invertible, which means its determinant should not equal zero—otherwise, the system has no unique solution. Happy calculating!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy